[+Agent] conditioned Case assignment to nominalized VPs in Korean LFN constructions - Keunhyung Park; Stanley Dubinsky (Linguistic research, 2021)
The aim of the current paper is to investigate how Case is assigned to non-canonical nominal expressions which are distinct from Case-marking on canonical subject and object arguments. More specifically, we focus on Case marking to nominalized verbs in Korean Long-Form negation constructions. As other nominal expressions get Case in Korean, the nominalized verbs with the -ci marker in Long-Form negation constructions can also get either NOM or ACC. However, the distributions of Case marking in this paper show that Case markers attached to the nominalized verbs are not randomly assigned, but it is systematically given depending on syntactic and semantic properties of the nominalized verbs. This paper proposes two distinct conditions as follows: the negated auxiliary verb anh (i) assigns only ACC Case to its nominalized verb complement or (ii) assigns either NOM or ACC Case allowing free Case alternation. To solve the puzzle of distinct Case assignment, this paper argues that agentivity is the important factor in deciding Case marking on the nominalized verb. Evidence from the data further proves that if nominalized verbs have +Agent feature, then the feature can percolate up to the Case assigner anh, and it eventually forces to assign only ACC Case back onto the nominalized verb. If not, the auxiliary verb anh cannot have +Agent feature and assigns either NOM or ACC. (University of South Carolina)